SOCIAL CHANGES IN THE REPUBLIC OF UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2024)
The article analyzes effective reforms in the social sphere in Uzbekistan, the issue of social protection of the population during the transition to a market economy, the main goal of all the reforms being carried out in the country, and today's issues of labor protection.